A realist evaluation of a multifactorial falls prevention programme in care homes. (5th December 2022) - Leighton, Paul A; Darby, Janet; Allen, Frances; Cook, Marie; Evley, Rachel; Fox, Chris; Godfrey, Maureen; Gordon, Adam; Gladman, John; Horne, Jane; Robertson, Kate; Logan, Pip
Abstract: Background: falls in care homes are common, costly and hard to prevent. Multifactorial falls programmes demonstrate clinical and cost-effectiveness, but the heterogeneity of the care home sector is a barrier to their implementation. A fuller appreciation of the relationship between care home context and falls programme delivery will guide development and support implementation. Methods: this is a multi-method process evaluation informed by a realist approach. Data include fidelity observations, stakeholder interviews, focus groups, documentary review and falls-rate data. Thematic analysis of qualitative data and descriptive statistics are synthesised to generate care home case studies. Results: data were collected in six care homes where a falls programme was trialled. Forty-four interviews and 11 focus groups complemented observations and document review. The impact of the programme varied. Five factors were identified: (i) prior practice and (ii) training may inhibit new ways of working; (iii) some staff may be reluctant to take responsibility for falls; (iv) some may feel that residents living with dementia cannot be prevented from falling; and, (v) changes to management may disturb local innovation. In some care homes, training and improved awareness generated a reduction in falls without formal assessments being carried out. Conclusions: different aspects of the falls programme sparked different mechanisms in different settings, with differing impact upon falls. The evaluation has shown that elements of a multifactorial falls programme can work independently of each other and that it is the local context (and local challenges faced), which should shape how a falls programme is implemented.